2017
DOI: 10.1186/s12889-016-3935-7
|View full text |Cite
|
Sign up to set email alerts
|

The social determinants of tuberculosis treatment adherence in a remote region of Papua New Guinea

Abstract: BackgroundPapua New Guinea (PNG) is a diverse and culturally-rich country with severe infrastructural and health problems. Tuberculosis (TB) is widespread, and the number of cases with drug resistance is rising. Treatment adherence is known to be important for both effective treatment and limiting the emergence of drug resistance. The aim of this study was to construct a matrix of the factors that act as facilitators or barriers to TB treatment adherence in a remote region of PNG.MethodsThe study was based in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 21 publications
2
29
0
2
Order By: Relevance
“…Treatment outcomes were unknown for just over 25% of patients who completed treatment at least 6 months before the end of the study period. This proportion may reflect the flexibility with which DOTS is often administered in the region, where patients may take their treatment packs back to their home village for the duration of treatment [6]. In this study, the only factor found to be significantly associated with poorer treatment outcomes was the LLG area in which a patient resided, with poorer outcomes more likely in the rural LLGs.…”
Section: Discussionmentioning
confidence: 78%
“…Treatment outcomes were unknown for just over 25% of patients who completed treatment at least 6 months before the end of the study period. This proportion may reflect the flexibility with which DOTS is often administered in the region, where patients may take their treatment packs back to their home village for the duration of treatment [6]. In this study, the only factor found to be significantly associated with poorer treatment outcomes was the LLG area in which a patient resided, with poorer outcomes more likely in the rural LLGs.…”
Section: Discussionmentioning
confidence: 78%
“…To improve treatment outcomes, further action is needed to strengthen patient support, including daily treatment, monitoring, counselling and continued efforts to strengthen the health system and address socioeconomic and physical barriers to accessing TB services. ( 17 ) Family DOT and self-administration are currently practised in Papua New Guinea but have not led to improved treatment success rates. Revisiting the care modality by strengthening community involvement and using an informal health workforce for treatment support is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…They were awareness about TB, motivation, employment, treatment duration, family, community and government support, stigma and discrimination and belief systems. Similar studies were conducted and concluded that patient adherence to their medication regimens was influenced by the interaction of personal and social factors [6] [11].…”
Section:  Disaster Prone Areasmentioning
confidence: 65%
“…The study results reflected the influence of traditional beliefs that resulted in delayed seeking care and showed the importance of communication and lack of stigma in the care of TB. A large number of patients had no stigma because of caste and TB [11] [14] [15].…”
Section:  Disaster Prone Areasmentioning
confidence: 99%
See 1 more Smart Citation